Clientelistic linkages in the Western Balkans: DALP II expert survey evidence - Bliznakovski Jovan (Anali Pravnog Fakulteta u Beogradu)
This paper examines the role of clientelism as a mobilization strategy in the Western Balkans, focusing on its interplay with other linkage strategies and its two primary sub-types: electoral and relational clientelism. Drawing on data from the Democratic Accountability and Linkages Project II (DALP II) expert survey, the study covers six party systems: Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia, and Serbia. The findings reveal that clientelism is one of the most frequently employed strategies in the region, characterized by durable linkages between parties, brokers, and voters, the distribution of public resources, significant use of negative inducements, and targeting across income groups. Relational clientelism, or patronage, emerges as the dominant form, extending beyond electoral goals to function as an organizing principle within party structures. This paper contributes to the understanding of clientelism in the region and highlights its implications for democratic accountability and governance.